Cellular immune response to hepatitis-C-virus in subjects without viremia or seroconversion: is it important?. Issue 1 (December 2016) - Abdelwahab, Sayed
Abstract Hepatitis C Virus (HCV) causes chronic infection and represents a global health burden. To date, there is no licensed vaccine for HCV. The high viral replication rate and the existence of several HCV genotypes and quasispecies hamper the development of an effective universal vaccine. In this regard, the current HCV vaccine candidates show genotype-specific protection or narrow cross reactivity against other genotypes. Importantly, HCV spontaneous clearance occurs in 15–50 % of infected subjects, indicating that natural resistance to chronic infection exists. This phenomenon was demonstrated among humans and chimpanzees and continues to motivate researchers attempting to develop an effective HCV vaccine. However, what constitutes a protective immune response or correlate of protection against HCV infection is still vague. Additionally, the mechanisms behind successful HCV clearance suggest the coordination of several arms of the immune system, with cell-mediated immunity (CMI) playing a crucial role in this process. By contrast, although neutralizing antibodies have been identified, they are isolate-specific and poorly correlate with viral clearance. Antigen-specific CD4 T cells, instead, correlate with transient decline in HCV viremia and long-lasting control of the infection. Unfortunately, HCV has been very successful in evading host immune mechanisms, leading to complications such as liver fibrosis, cirrhosis and hepatocellular carcinoma. Interestingly, CMI to HCV antigens were shown among exposed individuals without viremia or seroconversion, suggesting the clearance of prior HCV infection(s). These individuals include family members living with HCV-infected subjects, healthcare workers, IV drug users, and sexual contacts. The correlates of protection could be closely monitored among these individuals. This review provides a summary of HCV-specific immune responses in general and of CMI in particular in these cohorts. The importance of these CMI responses are discussed.